2015
DOI: 10.1038/bjc.2015.84
|View full text |Cite
|
Sign up to set email alerts
|

Hairy/enhancer-of-split related with YRPW motif protein 1 promotes osteosarcoma metastasis via matrix metallopeptidase 9 expression

Abstract: Background:Activation of the Notch pathway has been reported in various types of cancers. However, the role of the hairy/enhancer-of-split related with YRPW motif protein 1 (HEY1) in osteosarcoma is unknown. We examined the function of HEY1 in osteosarcoma.Methods:Expression of HEY1 was studied in human osteosarcoma. The effects of HEY1 in osteosarcoma were evaluated in vitro and in a xenograft model. Moreover, we examined the function of matrix metallopeptidase 9 (MMP9) as a downstream effector of HEY1.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…All of these studies showed that OS cells with higher metastatic potential have higher basal levels of notch receptors, especially notch-1, notch-2, notch ligands (Dll-1/Jagged-1), and notch target genes such as hey-1 and hes-1, as compared to normal osteoblasts or non-metastatic OS cell lines. Higher expression levels of these notch signaling associated genes or proteins were shown to be involved in invasiveness and metastasis and thus in impacting OS patient survival [16, 17]. Increased levels of jagged-1 in OS cells promote bone metastasis by activating stromal notch signaling.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these studies showed that OS cells with higher metastatic potential have higher basal levels of notch receptors, especially notch-1, notch-2, notch ligands (Dll-1/Jagged-1), and notch target genes such as hey-1 and hes-1, as compared to normal osteoblasts or non-metastatic OS cell lines. Higher expression levels of these notch signaling associated genes or proteins were shown to be involved in invasiveness and metastasis and thus in impacting OS patient survival [16, 17]. Increased levels of jagged-1 in OS cells promote bone metastasis by activating stromal notch signaling.…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Therefore, abolishing expression of hey-1, hes-1, notch-1, and jagged-1 by using γ-secretase inhibitors (GSI) also abolished their direct/indirect effects on survival, bone metastasis, and invasiveness in OS [16, 18]. These findings suggest that inhibiting notch signaling at various points may be a novel therapeutic strategy for preventing OS invasiveness and metastasis [17]. …”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Subsequently, Hey proteins were found to be involved in tumor metastasis progression. In vitro, Hey1 knockdown inhibited the invasive phenotype of osteosarcoma via downregulation of MMP9 (16). Furthermore, the transfection of Hey1 antisense oligonucleotides blocked EMT through E-cadherin expression, and Smad3 inhibition repressed Hey1-induced EMT phenotype even in the presence of TGFb (30).…”
Section: The Roles Of Hey Proteins In Cancer Metastasismentioning
confidence: 92%
“…However, the fact that HeyL differs in one of the key motifs, namely the YHSW motif, from Hey1 and Hey2 which both have the YRPW motif, may be one of the reasons why it acts differently from other Hey proteins. While YRPW appears to be a good target (16), YHSW, at least in hepatocellular carcinoma, may not be. This is clearly a fascinating area to explore, both in research and in clinical settings.…”
Section: The Roles Of Hey Proteins In Cancer Metastasismentioning
confidence: 99%
See 1 more Smart Citation